2013
DOI: 10.1371/journal.pone.0083443
|View full text |Cite
|
Sign up to set email alerts
|

The Numbers Tell It All: Students Don't Like Numbers!

Abstract: Undergraduate Students' interest in taking quantitative vs. non quantitative courses has received limited attention even though it has important consequences for higher education. Previous studies have collected course interest ratings at the end of the courses as part of student evaluation of teaching (SET) ratings, which may confound prior interest in taking these courses with students' actual experience in taking them. This study is the first to examine undergraduate students' interest in quantitative vs. n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 7 publications
2
21
0
2
Order By: Relevance
“…For example, Orpwood & Brown (2015) cite the 2013 OECD survey showing that numeracy among Canadians declined over the last decade and that more than half of Canadians now score below the level required to fully participate in a modern society. We found that students’ interest in taking quantitative courses such as introductory statistics was six standard deviations below their interest in taking non-quantitative courses ( Uttl, White & Morin, 2013 ). Fewer than 10 out of 340 students indicated that they were “very interested” in taking any of the three statistics courses.…”
Section: Discussionmentioning
confidence: 91%
“…For example, Orpwood & Brown (2015) cite the 2013 OECD survey showing that numeracy among Canadians declined over the last decade and that more than half of Canadians now score below the level required to fully participate in a modern society. We found that students’ interest in taking quantitative courses such as introductory statistics was six standard deviations below their interest in taking non-quantitative courses ( Uttl, White & Morin, 2013 ). Fewer than 10 out of 340 students indicated that they were “very interested” in taking any of the three statistics courses.…”
Section: Discussionmentioning
confidence: 91%
“…The Course Interest Survey [ 37 ] consisted of 44 titles and descriptions of all psychology courses offered in the 2012–2013 Mount Royal University calendar except the two introductory psychology first year courses that participants were registered in. The participants rated their interest in taking each course using a 5-point scale ranging from 1 = Not at all interested to 5 = Very interested .…”
Section: Methodsmentioning
confidence: 99%
“…A first self-regulatory factor, effort regulation, can be defined as persistence and effort when faced with academic challenges (Richardson, Abraham, and Bond 2012). Given that most students will at some point in their academic career encounter subjects that they deem less interesting (Uttl, White, and Morin 2013) or even anxiety-provoking (Onwuegbuzie and Wilson 2003), the ability to sustain attention and effort in the face of distractions or uninteresting tasks seems to be a key factor in achieving academic success (Komarraju and Nadler 2013).…”
Section: Self-regulatory Factorsmentioning
confidence: 99%